Characteristics of Rangin Cake Made of Various Kinds of Flour - Masashoumy Pasparingi; Lukman Hudi (Nabatia, 2014)
Food diversification, especially for rice-based food has been found by all society for our country’s food security soon be realized. One of such effortwas to develop the traditionalsnack-substitute rice flour as raw materials with different flours of local plant tuber such as cassava, white sweet potato, arrowroot, canna bulbs, purse, breadfruit and yellow squash. Aim of this study wasto determine the substitution effect of rice flour (Oryza sativa) with severalcake flours against to rangin. Experiment was arranged by randomized block design (RBD) using 9 kinds of flour (rangin cake ingredients): white sweet potato, cassava, purse, canna, arrowroot, mocaf, breadfruit, pumpkin and rice as the control, whichwere repeated intriplicate, in order to obtain 27 experimental units. The observed parameters were chemical analysis (concentration of amylose), physical analysis (elasticity and volume expansion) and sensory evaluations (color, aroma, flavor and texture). The data was analyzed using ANOVA followed by HSD test 5 % andsensory evaluation was analyzed by friedman test. Substitution of rice flour with various flourswas significantly different inconcentration of amylose content and volume expansion as well as sensory evaluation, such as color, aroma, taste and texture. The best characteristic of powder to substitute the rangin cake was tapioca. The characteristic based on concentration of amylose and volume expansionwere 55.21 % and 6.4 %, respectively.Its sensory characteristic based on color, aroma, flavor and texture were 4.9(rather like), 4.7 (rather like), 4.2 (normal), and 4.2 (normal), respectively.